Étude qualitative des High Rising Terminals à Dublin : protocole PAC-Prosodie et positionnements énonciatifs - Julia Bongiorno (Anglophonia)
This article presents the PAC Prosody protocol and demonstrates its interests when studying stance-taking from a suprasegmental perspective. We will show how the protocol can be used in a qualitative study on High Rising Terminals (HRTs) in the South of Dublin, Ireland. HRTs are rising tones that have a stylistic purpose and that appear at the end of statements. They can have different meanings depending on the speakers and have various phonetic forms depending on the variety of English in which they appear. In this article, we will show the usefulness of the different tasks of the protocol when studying varieties of English and their prosody. We will highlight how important a continuum in the ecological value of the data is for a thorough study of the different pragmatic functions of intonation. After introducing the PAC Program (Phonologie de l’Anglais Contemporain / Phonology of Contemporary English) and the PAC-Prosody methodology together with its advantages, aims, and utility, we will give a general overview of the various studies on HRTs in several varieties of English before focusing on the South of Dublin. In this article, we will show that the speech context is a decisive factor in the frequency of HRT in South Dublin, and that these rising tones are more frequent when the tasks are less controlled. We will also demonstrate that HRT rises are different from interrogative rises in the south of the Irish capital. Indeed, HRTs appear later, are steeper, and end up higher in the speakers’ pitch ranges. More generally, we will show how protocols such as PAC Prosody can be very useful when working on stance-taking in the prosody of varieties of English.